THE ANALYSIS OF INTERINCISAL AND VERTICAL ANGLES ON CONVEX FACIAL PROFILE ACCORDING TO STEINER (STUDY OF JAVANESE ORTHODONTIC PATIENTS IN BANYUMAS REGENCY) - Aisyah Dewi Kusuma, Nur; Handayani, Fani Tuti; Budi Purnama, Ryana; Taqwim, Ali; Rachel Keshena, Jatu (Journal of Vocational Health Studies, 2023)
Background: Orthodontic treatment focuses on correcting abnormal teeth and jaw positions for better facial esthetics. Abnormal teeth can be corrected by interincisal angle, while vertical angle can determine the facial growth pattern. Purpose: Analyze the interincisal and vertical angles on convex facial profiles of Javanese orthodontic patients in the Banyumas Regency. Method: Analytical descriptive research was conducted with a cross-sectional design. A purposive sampling technique was used to obtain lateral cephalograms totaling 33 based on inclusion and exclusion criteria from three locations. The lateral cephalogram was traced using tracing paper, while the interincisal and vertical angles were measured based on Steiner's analysis. Two operators carried out measurements, starting with tracing validation and the Kappa test. Furthermore, the results were from the average measurement of the two operators. Result: The mean interincisal and vertical angles were 115.30° and 37.04° with a protrusive inclination and hyperdivergent face, respectively. The correlation test showed a p-value of 0.432 (p > 0.05), meaning there was no relationship between the interincisal and vertical angles in Javanese orthodontic patients. Conclusion: There is no relationship between the interincisal and vertical angles in the convex facial profile of Javanese orthodontic patients in the Banyumas Regency.